Fibroblast Growth Factor-23 and Cardiovascular Disease in Chronic Kidney Disease - Utamawatin, Komchan; Satirapoj, Bancha (Journal of the Nephrology Society of Thailand, 2025)
Cardiovascular disease is the leading cause of death in patients with chronic kidney disease (CKD). Fibroblast growth factor 23 (FGF23) is a medium-sized uremic toxin that begins to accumulate as early as CKD stage 2, increasing progressively as glomerular filtration rate declines. This accumulation results from both increased production and reduced clearance of FGF23. The molecule binds to receptors on cardiac myocytes, triggering fibrotic signaling pathways that lead to myocardial hypertrophy and fibrosis. This cardiac remodeling heightens the risk of arrhythmias, heart failure, and cardiovascular mortality in CKD patients. Although significant progress has been made in understanding the regulation and biological actions of FGF23, effective treatments to reduce FGF23 levels or reverse cardiac remodeling remain limited. This article reviews the current understanding of FGF23 regulation and explores potential strategies to reduce its levels in order to improve cardiovascular outcomes in patients with CKD.